DistilBERT with Adam Optimizer Tuning for Text-based Emotion Detection - Farica Perdana Putri (IJNMT (International Journal of New Media Technology), 2023)
Emotion detection (ED) refers to identifying individual emotions or feelings, such as happiness, sadness, disappointment, fear, etc. The classic machine learning technique still relies on feature engineering, which makes it difficult to convey the meaning of words. Deep learning-based algorithms have recently been shown to be beneficial for emotion detection because they require only a simple feature creation process. Transfer learning is an approach that uses data similarities, data distribution, models, tasks, and other factors to apply knowledge learnt in one domain to a new domain. This study is to shed light on the fine-tuned models' efficacy in detecting emotions from the International Survey on Emotion Antecedents and Reactions (ISEAR) dataset. In order to optimize the model, we conducted the hyperparameters tuning on Adam optimizer in DistilBERT. The experiment examined the moment estimators and learning rate of Adam optimizer. The effect of the parameters to training and validation accuracy were presented and analyzed.